Upregulation of Bcl-2 and Its Promoter Signals in CD4+ T Cells during Neuromyelitis Optica Remission - Yang, Tao; Wang, Su; Yang, Xiao; Zheng, Qi; Wang, Lei; Li, Qian; Wei, Mingyan; Du, Zongpan; Fan, Yongping (Frontiers in Neuroscience, 2017)
The homeostatic balance between production and elimination of CD4+ T cells in peripheral blood plays an important role in patients with neuromyelitis optica (NMO). The objective of the present study was to evaluate the anti-apoptosis genes Bcl-2 and its promoter signal (nuclear factor kappa-light-chain-enhancer of activated B cells, NFκB) in CD4+ T cells. Healthy subjects (HS, n = 25) and patients with multiple sclerosis (MS) (n = 25) and NMO (n = 30) in remission were consecutively enrolled in this prospective study between May and December 2015. CD4+ T cells were isolated using magnetic beads coated with anti-CD4 monoclonal antibodies, and gene expression of Bcl-2, NFκB, phosphatidylinositol-4, 5-bisphosphate 3-kinase/protein kinase B (PI3K/Akt), and MAP kinase kinase kinase 7 (MAP3K7) was measured by real-time reverse transcription-polymerase chain reaction (rt-PCR). Cytokines of tumor necrosis factor (TNF)-α and interleukin (IL)-1β were detected using human cytokine multiplex assay. Bcl-2 and NFκB gene expressions were elevated in NMO patients (1.63±0.25; 2.35±0.25) compared with those of HS (0.90±0.11; 1.42±0.22) and/or MS patients (1.03±0.18; 1.55±0.20) (P<0.05). MAP3K7, but not Akt, was increased in NMO patients (1.23±0.18; 1.56±0.22) (P<0.01) and was a significant factor related to elevated NFκB gene expressions (P<0.001). On the other hand, IL-1β and TNF-α were also detected in the study and the results showed that both were elevated in NMO patients (23.84±1.81; 56.40±2.45) (P<0.01; P<0.05, respectively). We propose that MAP3K7 induced by IL-1β and TNF-α but not Akt promotes NFκB expression and, in turn, prolongs Bcl-2–mediated survival of CD4+ T cells in NMO patients.